The Development of an African Working Class - Dussault, Gilles (Relations industrielles / Industrial Relations, 1977)
This article reviews "The Development of an African Working Class" by R. Sandbrook and R. Cohen.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z